2020
DOI: 10.1002/ejlt.202000004
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Product from Low Pressure Extraction (Crambe Seed Oil and Methyl Acetate) for Synthesis of Methyl Esters and Triacetin Under Supercritical Conditions

Abstract: Methyl esters (ME) and triacetin production from the supercritical interesterification of the product from low pressure extraction (crambe seed oil and methyl acetate) are evaluated. Reactions are conducted at 300-375°C for different residence times, at 20 MPa, and under these conditions the thermal stability of triacetin is evaluated. The effect of the free fatty acid (FFA) concentration (in oil) is determined. An increase in temperature favors the formation of ME and triacetin at shorter reaction times. At 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 75 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…To determine the fatty acid composition of the DSA, ASA, and visceral adipose tissues, lipids were extracted from approximately 0.5 g of adipose tissue using chloroform. Lipid methyl esters were obtained by saponification with 2 mL hexane, 40 μL methyl acetate, and 100 μL sodium methoxide solution ( Postaue et al., 2020 ). Next, the fatty acids were analyzed using an Agilent 7890A Gas Chromatograph (Agilent Technologies Inc., Santa Clara, CA, USA) with a chromatographic column, according to the method previously described by Liu et al.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the fatty acid composition of the DSA, ASA, and visceral adipose tissues, lipids were extracted from approximately 0.5 g of adipose tissue using chloroform. Lipid methyl esters were obtained by saponification with 2 mL hexane, 40 μL methyl acetate, and 100 μL sodium methoxide solution ( Postaue et al., 2020 ). Next, the fatty acids were analyzed using an Agilent 7890A Gas Chromatograph (Agilent Technologies Inc., Santa Clara, CA, USA) with a chromatographic column, according to the method previously described by Liu et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, there were variations in the percentages of different lipid compounds among the different feedstocks. [44][45][46] For instance, a study conducted by Gunawan et al [44] focused on fractionating Calophyllum inophyllum seed oil using a continuous counter current extraction method with hexane and methanol as solvents. The results of that study indicated a high content of TAG (63.91%), which was higher than the findings in this current study.…”
Section: Fractionation Of Lipids From the Black Soldier Fly Larvaementioning
confidence: 99%